Violence against women: perception and professional approach in primary health care during the Covid-19 pandemic - Bruna Odorcik; Brígida da Penha Ferraz; Karina Castilhos Bastos; Maira Rossetto (Universidade Federal de Santa Maria, 2021)
Objective: To analyze the approach of health professionals in the identification of violence against women and their perception of the cases during the Covid-19 pandemic in Family Health Centers. Method: Qualitative study carried out in two health units, through semi-structured interviews with 23 health professionals. Data were collected between November 2019 and February 2021, and organized with the use of content analysis. Results: the categories created showed that health professionals know how to identify the types of domestic violence, but need greater awareness to support, identify and report the cases. According to the perception of the health professionals during the pandemic, there was an increase in violence attributed to social distancing. Conclusion: it is necessary to improve networking, provide better training to health professionals, offering support and active listening skills to women who face situations of domestic violence.